Studi Kualitatif: Konformitas Teman Sebaya Terhadap Perilaku Judi Online Pada Mahasiswa - Shaztry Zalmy; Shefriana Putri Pulungan; Citra Rahma Deya; Muhammad Wahyudi; Messy Mardatillah; Nur Fhadilla Alfanissa Sutopo; Agitia Kurniati Asrila (CV. ITTC INDONESIA, 2026)
This study examines the relationship between peer conformity and online gambling addiction among adolescents. With the advent of digital platforms, gambling has become increasingly accessible, particularly for adolescents and young adults, leading to significant mental health risks. This study aims to investigate how peer influence impacts gambling behavior and the potential for addiction. A qualitative approach using Interpretative Phenomenological Analysis (IPA) was used to investigate individuals' lived experiences. Semi-structured interviews with university students who had engaged in online gambling were used. Findings indicate that peer pressure plays a significant role in motivating individuals to gamble online, often driven by a desire for social acceptance. Participants reported feeling compelled to conform to group norms, which reduced their self-control and awareness of the risks involved. The emotional need for belonging emerged as a significant factor influencing their decisions. Furthermore, this study highlights the detrimental psychological effects, including anxiety and depression, stemming from gambling-related stress. In conclusion, this study emphasizes the importance of understanding peer dynamics in preventing online gambling addiction. The insights gained can inform future interventions aimed at fostering resilience among adolescents and reducing the risks associated with online gambling. Readers are encouraged to explore social influences on individual behavior as they navigate this critical issue.